Animal behavior is central in shaping the realized diel light niche - N. Sören Häfker; Stacey Connan-McGinty; Laura Hobbs; David McKee; Jonathan H. Cohen; Kim S. Last (Communications Biology, 2022)
Investigating the light as experienced by zooplankton undergoing synchronized diel vertical migration in an Arctic fjord around the spring equinox provides insights into how animal behavior shapes the Realized Diel Light Niche.